Fight Hoaxes with Literation to Save Generations - Boer, Kheyene Molekandella; Dwivayani, Kadek Dristiana (Budapest International Research and Critics University, 2021)
The explosion of information in this era demands that the public must intervene to at least save themselves. Information moves so fast, which has been able to condition the public, including teenagers, as individuals who are always hungry for any information that impacts dependence on smartphones and social media. This condition is considered a nation's progress because it can be open to technological innovation. However, information technology gradually becomes a problem when there is an increase in false information, known as hoaxes, that dominate social media. Even information overlaps and reaches the public with unclear truth. Therefore, it is feared that the public will accept the essential information and ultimately act on the hoax they consume. Digital literacy is a method for forming public understanding in responding to hoax news. Before digesting the news, the public is expected to evaluate and provide an assessment of the type of news. Therefore, the government and social groups are now actively promoting digital literacy to counter hoax news to create better public quality and maintain Indonesia's unity and integrity.